PROBLEMS BETWEEN PARENTS AND CHILDREN - Firuza Sharipova; Abdikulova Shaxzodabonu Ilyosjon qizi (Journal of new century innovations, 2022)
Abstract:this article will focus on problems,conflicts and some disagreements between parents and children and their negative consequences as well as giving them suitable solutions.